Targeted Protein Degradation and Regulation with Molecular Glue: Past and Recent Discoveries - Fang, Yizheng; He, Qiaojun; Cao, Ji (Current Medicinal Chemistry, 2022)
The evolution in research and clinical settings of targeted therapies has been inspired by the progress of cancer chemotherapy to use small molecules and monoclonal antibodies for targeting specific disease-associated genes and proteins for noninfectious chronic diseases. In addition to conventional protein inhibition and activation strategies as drug discovery modalities, new methods of targeted protein degradation and regulation using molecular glues have become an attractive approach for drug discovery. Mechanistically, molecular glues trigger interactions between the proteins that originally did not interact by forming ternary complexes as protein-protein interaction (PPI) modulators. New molecular glues and their mechanisms of action have been actively investigated in the past decades. An immunomodulatory imide drug, thalidomide, and its derivatives have been used in the clinic and are a class of molecular glue that induces degradation of several neo-substrates. In this review, we summarize the development of molecular glues and share our opinions on the identification of novel molecular glues in an attempt to promote the concept and inspire further investigations.
Keywords: E7820